2014
DOI: 10.5114/ceji.2014.45936
|View full text |Cite
|
Sign up to set email alerts
|

Experimental immunology Cytokine signatures of human whole blood for monitoring immunosuppression

Abstract: How to evaluate status of the immune system is extremely critical for clinical immunosuppressive treatment. In this study, we tested the secretion of cytokines in undiluted whole blood samples stimulated with Phorbol 12-myristate 13-acetate (PMA) and ionomycin (IONO), and compared the effects of dexamethasone (DEX), cyclosporine A (CsA) or mycophenolic acid (MPA), either alone or in combination, on cytokine profiles. The results showed that both DEX and CsA dose-dependently inhibited the production of eleven c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Cytokine monitoring has been proven useful in selection of immunosuppressive therapy, prediction of graft rejection, and progression of various diseases involving immunological abnormalities ( 23 , 24 ). Previous studies have shown that IFN-γ production is a useful biomarker of graft dysfunction, cancer progression, and infectious disease prognosis ( 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine monitoring has been proven useful in selection of immunosuppressive therapy, prediction of graft rejection, and progression of various diseases involving immunological abnormalities ( 23 , 24 ). Previous studies have shown that IFN-γ production is a useful biomarker of graft dysfunction, cancer progression, and infectious disease prognosis ( 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, other authors did not find evidence of this expanded Th17 response in AAV [20, 21, 34]. It may be hypothesized this is due to a high susceptibility of this cellular subset to steroids, as a possible explanation [35], or due to the variety of cytokines in the IL-17 family. For instance, Krohn et al .…”
Section: T-lymphocytes: Imbalances and Dysfunction In Aavmentioning
confidence: 91%
“…Although TB+DM continued to show a remarkable response despite this steroid treatment. Cortisol inhibitory effects on pro-inflammatory cytokine production are achieved by several transcriptional repression mechanisms (93)(94)(95)(96)(97), with some inconsistencies as to its role in the production of anti-inflammatory mediators in light of evidence reporting a stimulating or inhibitory influences on IL-10 in vitro synthesis (98)(99)(100)(101)(102). Whether the present diminished IL-10 production is to some extent related to the decreased TNF-α and IFN-γ synthesis, which by themselves may promote IL-10 production (103), remains to be established.…”
Section: Discussionmentioning
confidence: 99%